Solution:
I'm not sure if there is law for it or not, but you can replace each x to -2 if both sides are equal then the equation is true.
[tex]7x - 4 = 6x + 5\\7(-2) - 4 = 6(-2) + 5\\-14-4=-12+5\\-18\neq -7[/tex]
A. is incorrect.
[tex]4x + 3 = 8x - 5\\4(-2) + 3 = 8(-2) - 5\\-8+3=-16-5\\-5\neq -21[/tex]
B. is incorrect.
[tex]6x + 4 = 3x + 10\\6(-2) + 4 = 3(-2) + 10\\-12+4=-6+10\\-8\neq 4[/tex]
C. is incorrect.
[tex]-5x - 3 = -7(x +1)\\-5(-2) - 3 = -7((-2) +1)\\10-3 =-7(-1)\\7=7[/tex]
D. is correct.
Answer:
D. [tex]-5x-3=-7(x+1)[/tex]
Hope this was helpful.